2011
DOI: 10.1021/ef201392s
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biofuels: Fluid Properties to Optimize Feedstock Selection, Processing, Refining/Blending, Storage/Transportation, and Combustion

Abstract: As the availability of petroleum-based liquid fuels is becoming increasingly problematic, alternative renewable biofuels attract growing research and development (R&D) and industry interest. The focus is to produce fuels with desired properties in both technically and economically attractive ways to support sustainability and protect the environment. While abundant, the variety of biomass feedstocks brings a great deal of incompatibility of various biofuels and the combustion engines. A consistent theme is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 186 publications
1
25
0
Order By: Relevance
“…Biodiesel-derived FFA was not available at the time of these experiments but would normally be available in the acidulation step in purification of glycerin. 1,32 Generally, we have found that ionic surfactants are more likely to be affected by the ash (ion) content of the crude glycerin. Weakly ionic carboxylate surfactants (such as TOFA) are negatively affected by high levels of ionic salts, which serve to counter dissociation of the surfactants.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Biodiesel-derived FFA was not available at the time of these experiments but would normally be available in the acidulation step in purification of glycerin. 1,32 Generally, we have found that ionic surfactants are more likely to be affected by the ash (ion) content of the crude glycerin. Weakly ionic carboxylate surfactants (such as TOFA) are negatively affected by high levels of ionic salts, which serve to counter dissociation of the surfactants.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…But the implementation and scale up of any candidate requires assessments of health [41], ground water contamination, biochemical/thermal stability [23], physical properties, blending compatibility with petroleum products [37,51,52], fuel system materials compatibility, and environmental reactivity [53]. Given past controversies in the United States over methyl tertbutyl ether (MTBE) [http://www.epa.gov/mtbe/] as a gasoline additive, it appears prudent to consider these matters prior to investing significantly in detailed fundamental and applied combustion research or production scale-up economics.…”
Section: Introductionmentioning
confidence: 99%
“…Given the different chemical composition of biofuels as compared to conventional petroleum-based fuels, soot aerosols may differ in terms of size, chemistry, morphology, reactivity to oxidation, and toxicological effects (Fukagawa et al, 2013;Lapuerta et al, 2012;Szybist et al, 2007). For instance, it is widely demonstrated that biofuels can change both the combustion dynamics and the formation of pollutants such as soot particles or nitrogen oxides (Abassi and Abassi, 2010; Anitescu et al, 2012;KohseHöinghaus et al, 2010;Lapuerta et al, 2008;Szybist et al, 2007). While the use of biofuels has been widely reported to reduce both soot particle volume fraction and sizes, and to increase the reactivity to oxidation, the modification of the soot nano-and microstructure is still under debate.…”
Section: Introductionmentioning
confidence: 99%